The effect of spin-orbit coupling on nonsymmorphic square-net compounds. (May 2019) - Topp, Andreas; Vergniory, Maia G.; Krivenkov, Maxim; Varykhalov, Andrei; Rodolakis, Fanny; McChesney, Jessica L.; Lotsch, Bettina V.; Ast, Christian R.; Schoop, Leslie M.
Abstract: In the field of Dirac materials, spin-orbit coupling (SOC) is usually considered disruptive, since it may lift degeneracies that are not protected by high-symmetry elements. Nonsymmorphic symmetries force degenerate points in the band structure at high-symmetry points that are not disrupted by SOC. The degeneracy is, however, often protected along whole high-symmetry lines or faces resulting in highly anisotropic crossings or nodal lines, which can considerably limit the region, in which the bands are linearly dispersed. It has been theoretically suggested that SOC could circumvent this problem. Here, we show experimentally that SOC can lift the extended protection in nonsymmorphic square-net compounds. We compare ZrSiS and CeSbTe, two materials with drastically different SOC, to show the effect of SOC on the band structure by means of angle-resolved photoemission spectroscopy and density functional theory calculations. Highlights: The effect of spin-orbit coupling in nonsymmorphic square-net materials is investigated We find that SOC can create more symmetric Dirac cones protected by nonsymmorphic symmetry SOC does not gap Dirac cone in nonsymmorphic compounds We conclude that in nonsymmorphic materials SOC can be a useful tuning parameter for creating Dirac Semimetals